Knowledge, attitudes and practices of food hygiene among mobile food vendors in a Nigerian rural settlement - Aluh, Francis Owoicho; Aluh, Deborah Oyine (International Journal Of Community Medicine And Public Health, 2017)
Background: An estimated 2.5 billion people patronize mobile food vendors worldwide. Most vendors however have little or no formal education, which makes them unable to appreciate the most critical food handling practices. Consumers have thus borne the consequences when food is unsafe. This study aims to determine the Knowledge, Attitudes and Practice of Food hygiene amongst mobile food vendors in a rural settlement Methods:It was a cross-sectional descriptive survey among the study population which comprised of mobile food vendors in Orlu Local Government Area in Imo state, Nigeria. Semi-Structured questionnaires written in English were administered to mobile food vendors who could read. For low literates, the interview was conducted in their local dialect by a trained research assistant Results: Respondents were mainly females (94.1%, n = 192) and between the age of 31 and 40 years (40.2%, n = 82). More than half of the respondents had secondary school education (59.8%,n = 122).The mean percentage knowledge was 78%. Less than half (43.5%, n = 89) of the respondents had an appropriate attitude towards Food hygiene. There was a strong evidence of association (χ2 = 15.582; p = 0.0001) between Knowledge of food hygiene and attitudes towards food hygiene. Conclusions: Knowledge levels of food safety practices amongst street food vendors in this rural setting was high however, this high knowledge was generally not translated into practice.